2022
DOI: 10.1097/aud.0000000000001255
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Universal Newborn Hearing Screening

Abstract: Design: Monocentric retrospective study whose target population included all the newborns born in or referred to our hospital in 2019 and 2020.Results: There is no statistically significant difference in time to retest or loss to follow-up rate between the 2 years considered (2019 to 2020). Referral rate is not higher for newborns born to severe acute respiratory syndrome coronavirus 2 polymerase chain reaction positive mothers. Conclusions:In relation to the analyzed variables, coronavirus disease 2019 seems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…We also find no difference in rates of follow-up for pre-pandemic versus pandemic-era newborns; comparable results were obtained in a study performed in Italy. 17 We find that the times to follow-up in the CHW intervention group versus non-intervention group were not significantly different. A potential explanation for this nondifference is the fact that CHWs helped families reschedule appointments when they could not attend on their original scheduled date.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We also find no difference in rates of follow-up for pre-pandemic versus pandemic-era newborns; comparable results were obtained in a study performed in Italy. 17 We find that the times to follow-up in the CHW intervention group versus non-intervention group were not significantly different. A potential explanation for this nondifference is the fact that CHWs helped families reschedule appointments when they could not attend on their original scheduled date.…”
Section: Discussionmentioning
confidence: 60%
“…Notably, we aimed to address disparities in the context of the COVID-19 pandemic, which has complicated follow-up screening in other countries. 17,18 In this study, we evaluate adherence to follow-up screening for families receiving an innovative CHW intervention versus families not receiving intervention; we aim to demonstrate that similar CHW interventions may be implemented more broadly across healthcare systems in the context of UNHS.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Gallus et al 10 demonstrated that despite hospital-imposed rules for patients and visitors, their screening program was not significantly affected by the COVID-19 pandemic. This is demonstrated by observing the time to retest after the initial failed NBHS and loss to follow-up between 2 groups of children.…”
Section: Discussionmentioning
confidence: 99%
“…The universal newborn hearing screening (UNHS) program of Azienda Ospedaliero Universitaria di Sassari implemented counseling after the initial NBHS and a proactive recall policy to minimize lost to follow-up. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation